2006
DOI: 10.2165/00044011-200626090-00004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Botulinum Toxin Type??A??in??the??Relief of Carpal??Tunnel??Syndrome

Abstract: Our data suggest long-lasting antinociceptive effects of botulinum toxin A rather than electrophysiological restoration in patients with CTS. Intracarpal injection of botulinum toxin A was shown to be well tolerated and safe. A double-blind, placebo-controlled trial of botulinum toxin A in CTS is warranted since the current study may have been confounded by the placebo effect of intracarpal injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…The investigators injected a total of 60 U intracarpally and followed the patients monthly for 3 months. [36] The patients experienced no weakness, unlike that seen in the study by Breuer et al, probably since the abobotulinumtoxinA was not injected into the muscle. While there was a trend toward pain improvement in three patients, the finding was not significant.…”
Section: Review Brown Schütz and Simpsonmentioning
confidence: 63%
See 1 more Smart Citation
“…The investigators injected a total of 60 U intracarpally and followed the patients monthly for 3 months. [36] The patients experienced no weakness, unlike that seen in the study by Breuer et al, probably since the abobotulinumtoxinA was not injected into the muscle. While there was a trend toward pain improvement in three patients, the finding was not significant.…”
Section: Review Brown Schütz and Simpsonmentioning
confidence: 63%
“…Based on one class I study [35] and one class IV study [36] that showed no significant effect on pain following BoNT injection for carpal tunnel syndrome pain, the use of BoNT is probably not effective (level B evidence) ( Table 4). …”
Section: Review Brown Schütz and Simpsonmentioning
confidence: 99%
“…The effect of epidural volume extension with 5 ml saline on spinal blockade as part of a combined spinal epidural technique in 90 term parturient undergoing elective CS has been reported as deprived of benefits 54 . Kucukguclu et al 55 .…”
Section: Tricksmentioning
confidence: 99%
“…The LANSS scale is a simple and suitable screening test for neuropathic pain in patients with HNC pain, (sensitivity 79%; specificity 100%), although some modifications might improve it. [54] Chemotherapy-induced painful peripheral neuropathies (CIPN) are increasing in frequency as more neurotoxic agents are introduced to treat cancer. Patients describe symmetrical, distal painful neuropathy in a ''stocking and glove'' distribution, usually in the feet/toes and fingers/hands/.…”
Section: Neuropathic Pain In Cancer Survivors Prevalence and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation